Developing multilingual practices in early childhood education through professional development in Luxembourg. Issue 4 (1st October 2020) - Kirsch, Claudine; Aleksić, Gabrijela; Mortini, Simone; Andersen, Katja
ABSTRACT: This paper investigates seven early education practitioners' attitudes toward multilingual activities and translanguaging as well as their actual practices in Luxembourg. They took part in a professional development comprising a course, coaching, and regular meetings to deepen their understanding of multilingualism and language learning, and enable them to implement activities in multiple languages. The findings, drawn from questionnaires, observations, and interviews, show that all practitioners opened up toward multilingual activities and translanguaging, increased activities in such languages, and translanguaged frequently. The practitioners analyzed their beliefs and practices, connected theory and practice, constructed new knowledge, developed positive attitudes and changed their practice. This study is the first one to investigate the attitudes and practices of professionals in formal and non-formal education settings as well as the effect of professional development in Luxembourg. It also addresses the research gap regarding professional development on multilingualism in early childhood.